1998
DOI: 10.1097/00004836-199807000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Do Back Support Belts Cause Gastroesophageal Reflux?

Abstract: A competent lower esophageal sphincter (LES) prevents gastroesophageal reflux disease (GERD) in the setting of increased abdominal pressure. Therefore, we have assessed whether a back support belt causes gastroesophageal reflux (GER). Ten healthy volunteers underwent esophageal manometric studies to locate the LES. Subsequently, each subject underwent two separate 8-hour intra-esophageal pH monitor studies on different days, the first without wearing a back support belt, and the subsequent one wearing a back s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…This result was concordant with result obtained by Yamagishi et al (22). Also, Sawaoka et al reported that both selective and non-selective COX-2 inhibitors exerted minimal effects on cell proliferation of human gastric cancer cell lines, which expressed lower levels of COX-2, but suppressed cell proliferation of human gastric cancer cell lines that overexpressed COX-2 (23). These results imply that COX-2 play a critical role in tumor cell proliferation of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This result was concordant with result obtained by Yamagishi et al (22). Also, Sawaoka et al reported that both selective and non-selective COX-2 inhibitors exerted minimal effects on cell proliferation of human gastric cancer cell lines, which expressed lower levels of COX-2, but suppressed cell proliferation of human gastric cancer cell lines that overexpressed COX-2 (23). These results imply that COX-2 play a critical role in tumor cell proliferation of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%